Morning Stiffness in Rheumatoid Arthritis: Investigating its Relationship with Disease Activity as Assessed by Power Doppler Ultrasonography and Composite Scores. Issue 3 (2nd October 2015) - Seki, Kazushige; Kanchiku, Tsukasa; Tokushige, Atsunori; Ogasa, Hiroyoshi; Imagama, Takashi; Seki, Toshihiro; Taguchi, Toshihiko
Abstract: Objective: This study investigated potential associations of morning stiffness (MS) with rheumatoid arthritis (RA) disease activity and ultrasonography (US). Methods: We conducted a cross-sectional analysis of 100 consecutive patients with RA divided into MS-positive group ( n  = 38) and MS-negative group ( n  = 62). US findings, disease activity score in 28 joints (DAS28) and Clinical Disease Activity Index (CDAI) were compared. Results: DAS28, CDAI and the number of power Doppler (PD) signal-positive joints were significantly higher in the MS-positive group ( p  < 0.01). The number of patients who did not achieve the DAS28 or CDAI remission criteria was significantly higher in the MS-positive group ( p  < 0.01). When cut-off points were applied, MS duration of ≥10 min was associated with PD signal-positive joints, with a sensitivity of 47.5% and a specificity of 92.3% (area under curve = 0.7087, chi-square test: p  < 0.0001). Conclusion: This study showed that in patients with MS duration of ≥10 min, there was a high probability of PD-positive joints in the hand.